Perioperative and Long-Term Smoking Behaviors in Cosmetic Surgery Patients. Issue 3 (September 2017) - Van Slyke, Aaron C.; Carr, Michael; Knox, Aaron D. C.; Genoway, Krista; Carr, Nicholas J.
Abstract : Background: Many plastic surgeons advocate smoking cessation before patients undergo cosmetic surgery with extensive soft-tissue dissection. Smoking cessation rates after cosmetic surgery are unknown. The preoperative consultation may be an opportunity to promote long-term smoking cessation. Methods: This is a retrospective, cross-sectional cohort study. All patients over an 8-year study period who smoked before their preoperative consultation; who quit 2 weeks before surgery; and who subsequently underwent rhytidectomy, abdominoplasty, or mastopexy were included. Patients were asked to complete a Web-based survey at long-term follow-up. Results: Eighty-five smokers were included, and 47 patients completed the survey, for a response rate of 55.3 percent. Average follow-up was 63.3 months. Five respondents were social smokers and thus excluded. Of the 42 daily smokers, 17 patients (40.5 percent) were no longer smoking cigarettes on a daily basis at long-term follow-up. Of these 17 patients, 10 (23.8 percent) had not smoked since their operation. A total of 24 patients (57.1 percent) had reduced their cigarette consumption by any amount, and 70.8 percent (17 of 24) of these patients agreed that discussing adverse surgical outcomes related to smoking influenced their ability to quit/reduce. Twenty-one of 42 patients (50.0 percent) admitted that they were not compliant with the preoperative smoking cessation instructions. Conclusions: This is the first report to investigate long-term smoking cessation from a cosmetic surgery practice. The authors have shown a positive association between smoking cessation and cosmetic surgery. Requesting a period of cessation before cosmetic surgery may promote long-lasting smoking cessation.